2016
DOI: 10.1371/journal.pone.0165523
|View full text |Cite
|
Sign up to set email alerts
|

FTO Gene Polymorphism Is Associated with Type 2 Diabetes through Its Effect on Increasing the Maximum BMI in Japanese Men

Abstract: AimSeveral studies have demonstrated that polymorphisms within the fat-mass and obesity-associated gene (FTO) are associated with type 2 diabetes (T2D). However, whether the effects of the FTO locus on T2D susceptibility are independent of fat-mass increases remains controversial. To investigate this issue, we examined the association of FTO variants with T2D and various aspects of BMI history during adult life in a Japanese population.MethodsWe genotyped SNPs within FTO (rs1121980 and rs1558902) in 760 Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…A recent study by Kamura et al [25] suggested that the association between FTO variants and T2D is mediated through the lifetime maximum BMI at the time of or before diagnosis of T2D. Nevertheless, our lack of association with the T2D risk has also been reported in populations of similar genetic background to the Kuwaiti population [26, 27].…”
Section: Discussionmentioning
confidence: 54%
“…A recent study by Kamura et al [25] suggested that the association between FTO variants and T2D is mediated through the lifetime maximum BMI at the time of or before diagnosis of T2D. Nevertheless, our lack of association with the T2D risk has also been reported in populations of similar genetic background to the Kuwaiti population [26, 27].…”
Section: Discussionmentioning
confidence: 54%
“…Its association with T2D was also reported (22). The effects of FTO polymorphisms on T2D susceptibility may be mediated through their effect on increasing the lifetime maximum BMI before or at the time of diagnosis (23). However, in two metaanalysis on GDM, no associations between FTO polymorphisms (rs9939609, rs8050136, rs1421085, rs9939609, and rs8050136) and GDM risk were found (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not observe any possible haplotype associated with T2DM in the strong linkage disequilibrium region (block 1). While some other studies showed there were strong association between FTO variants and T2DM [10,[27][28][29][30][31]. The different ethnicities and race, cross-sectional design, and small sample size may lead to inconsistent results.…”
Section: Discussionmentioning
confidence: 96%